Ownership structure and firm performance: Evidence manufacturing companies listed in Dhaka Stock Exchange - S. M. Khaled Hossain; Md. Imtiaz Sultan; Md. Mekail Ahmed (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aims at examining the relationship between ownership structure and firm performance about manufacturing companies listed in Dhaka Stock Exchange (DSE). Research Methodology: The analysis empirically uses dynamic panel data from 15 pharmaceutical and chemical companies enlisted in Dhaka Stock Exchange (DSE). The study period was 2011-2020. The study used panel data regression analysis. Results: The study confirms that sampled companies' financial performance represented by ROA and ROE is significantly influenced by institutional ownership, ownership concentration, and foreign ownership whereas, negatively influenced by managerial ownership and insider ownership. The study didn't find any noteworthy association between block holders' ownership with firms' performance. Contribution: This study keeps a significant role in understanding the ownership structures’ influence on firms’ performance. More specifically the policymakers may consider the study for implementing the relevant issues. Limitations: The study's results were restricted to 15 Bangladeshi pharmaceutical and chemical companies enlisted in DSE and could not be applied to other companies doing business in Bangladesh.